2021
DOI: 10.1021/acs.bioconjchem.1c00420
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Cargo Encapsulation into Virus Protein Cages by Self-Assembly in an Aprotic Organic Solvent

Abstract: While extensive studies of virus capsid assembly in environments mimicking in vivo conditions have led to an understanding of the thermodynamic driving forces at work, applying this knowledge to virus assembly in other solvents than aqueous buffers has not been attempted yet. In this study, Brome mosaic virus (BMV) capsid proteins were shown to preserve their self-assembly abilities in an aprotic polar solvent, dimethyl sulfoxide (DMSO). This facilitated protein cage encapsulation of nanoparticles and dye mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In a study conducted by Xie et al [90], the self-assembly abilities of Brome mosaic virus (BMV) capsid proteins were investigated in the aprotic polar solvent dimethyl sulfoxide (DMSO), which differs from the typical aqueous buffers used in previous studies. The researchers observed that the BMV capsid proteins retained their ability to self-assemble in DMSO, enabling the encapsulation of nanoparticles and dye molecules that are more soluble in organic solvents, such as β-NaYF4-based UCNPs and BODIPY dye.…”
Section: Synthesis Of Lnpsmentioning
confidence: 99%
“…In a study conducted by Xie et al [90], the self-assembly abilities of Brome mosaic virus (BMV) capsid proteins were investigated in the aprotic polar solvent dimethyl sulfoxide (DMSO), which differs from the typical aqueous buffers used in previous studies. The researchers observed that the BMV capsid proteins retained their ability to self-assemble in DMSO, enabling the encapsulation of nanoparticles and dye molecules that are more soluble in organic solvents, such as β-NaYF4-based UCNPs and BODIPY dye.…”
Section: Synthesis Of Lnpsmentioning
confidence: 99%
“…Substantial efforts are being made to utilize multimeric, self-assembling protein complexes in bionanotechnological applications [ 1 , 2 , 3 , 4 , 5 ]. Nanodimensional cage-proteins such as ferritins [ 6 , 7 ], cavity-containing enzymes [ 8 ], chaperonins [ 9 ], virus capsids [ 10 , 11 , 12 ], vault proteins [ 13 , 14 ], microbial microcompartments [ 15 , 16 , 17 ], and encapsulins [ 18 ] can be engineered with some precision to accommodate guest molecules within their hollow interior cavities. The strategic design of protein cages has resulted in the creation of biomolecular platforms capable of encapsulating a diverse set of guest molecules ranging from drugs [ 8 , 19 ], metal nanoparticles [ 20 , 21 ], enzymes [ 22 , 23 ], polymers [ 24 , 25 ], and oligonucleotides [ 26 ].…”
Section: Introductionmentioning
confidence: 99%